Sorgo grão e a suplementação de carotenoides em rações para frangos de corte - Litz, Fernanda Heloisa (2018)
The demand for alternative energy ingredients to be used in animal feed is constant, and sorghum stands out as a good substitute for corn. This study aimed to evaluate the use of grain sorghum in different granulometries and the inclusion of synthetic carotenoids in broiler diets on performance, carcass yield, intestinal morphometry and meat quality. This study was developed in a completely randomized design, consisting of four experimental feed: corn (M), ground sorghum (SM) and the inclusion of synthetic carotenoids (SMC) and whole sorghum (SI), all of them isoenergetic and isonutrients, using 960 birds, males and females, being 240 per treatment. The following variables were analyzed: body weight, feed intake, real and traditional feed conversion, carcass and cut yield, gizzard and small intestine weight; to evaluate meat quality were analyzed the pH at four and 24 hours post-mortem, cooking losses, shear force, colorimetry and centesimal composition of broilers breast meat. The SI feed provided a greater gizzard development, although at 7 days there were no differences in body weight and feed conversion between diets. The SM and SMC provided higher values of body weight at 28 days than SI. The real and traditional feed conversions at 40 days were the same for sorghum feeds, with better carcass yield in SM and SMC. There were no differences in the variables pH at 4 hours post mortem, PPC and FC. The value of pH 24 hours post mortem was lower for corn compared to SM and SI feed and similar to inclusion of carotenoids. For luminosity and tendency to red the SMC breast fillet was statistically different from the corn feed, but in tendency to yellow reached the same value of the corn and both larger than the SM and SI. The carotenoids inclusion in the diet provided a breast meat with higher protein content compared to corn and lower fat content among all the feeds tested. It can be concluded that ground sorghum can completely replace corn in broiler diets without compromising performance, carcass yield and quality parameters, and in the coloring matter, with the carotenoid addition the same pattern of corn diets is achieved besides having a lower fat content in the breast musculature. It is also worth noting that whole grain sorghum is zootechnically viable besides the economic benefit in feeds processing.